T cell intrinsic STAT1 signaling prevents aberrant Th1 responses during acute toxoplasmosis - Schultz, Aaron B.; Kugler, David G.; Nivelo, Luis; Vitari, Nicolas; Doyle, Laura P.; Ristin, Svetlana; Hennighausen, Lothar; O’Shea, John J.; Jankovic, Dragana; Villarino, Alejandro V. (Frontiers in Immunology, 2023)
Infection-induced T cell responses must be properly tempered and terminated to prevent immuno-pathology. Using transgenic mice, we demonstrate that T cell intrinsic STAT1 signaling is required to curb inflammation during acute infection with Toxoplasma gondii. Specifically, we report that mice lacking STAT1 selectively in T cells expel parasites but ultimately succumb to lethal immuno-pathology characterized by aberrant Th1-type responses with reduced IL-10 and increased IL-13 production. We also find that, unlike STAT1, STAT3 is not required for induction of IL-10 or suppression of IL-13 during acute toxoplasmosis. Each of these findings was confirmed in vitro and ChIP-seq data mining showed that STAT1 and STAT3 co-localize at the Il10 locus, as well as loci encoding other transcription factors that regulate IL-10 production, most notably Maf and Irf4. These data advance basic understanding of how infection-induced T cell responses are managed to prevent immuno-pathology and provide specific insights on the anti-inflammatory properties of STAT1, highlighting its role in shaping the character of Th1-type responses.